2020
DOI: 10.1111/jpc.15116
|View full text |Cite
|
Sign up to set email alerts
|

Educating paediatric health‐care providers about human trafficking

Abstract: Human trafficking is a public health issue and humanitarian crisis. Most alarming is that children are especially at risk. Although many studies demonstrate that the majority of trafficked persons surveyed engage with the health‐care system during the time in which they are trafficked, health‐care practitioners lack the knowledge, tools and resources to assist these patients. The present efforts in training health‐care professionals have been fragmented and largely ineffective. While prior training has produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A multidisciplinary approach needs to be undertaken in collaboration with service organizations. The health care provider can act as a liaison between the trafficking survivor and the social services sector; however, the social service providers need to be ready to mobilize and provide shelter, meals, and rehabilitative services (Coughlin, Greenbaum, & Kitchen, 2020; Kennedy et al, 2021; Schwarz et al, 2016). At present, most facilities do not have programs and policies in place to facilitate this multidisciplinary approach (Rollins, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multidisciplinary approach needs to be undertaken in collaboration with service organizations. The health care provider can act as a liaison between the trafficking survivor and the social services sector; however, the social service providers need to be ready to mobilize and provide shelter, meals, and rehabilitative services (Coughlin, Greenbaum, & Kitchen, 2020; Kennedy et al, 2021; Schwarz et al, 2016). At present, most facilities do not have programs and policies in place to facilitate this multidisciplinary approach (Rollins, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Educational interventions are a successful means to enhance the knowledge of providers. However, it is unclear whether providing education results in a meaningful increase in ability to recognize and assist survivors (Berishaj et al, 2019; Coughlin et al, 2020).…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…The mean scores improved from 69.2 to 89.2, showing statistical significance (<.001). These findings are significant because education targeted to health care providers may increase the number of human trafficking victims identified in clinical practice and may improve the quality of care for this vulnerable population (Coughlin et al, 2020; Donahue et al, 2019; Gibbons & Stoklosa, 2016; Miller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Victims of human trafficking experience or are placed at risk for negative and life-altering health consequences including physical trauma, sexually transmitted infections, acute medical conditions, pregnancy-related issues, and exacerbations of untreated chronic diseases. Trafficked individuals may also experience psychiatric emergencies including major depression, suicidality, toxidromes, substance use disorders, and anxiety (McAmis et al, 2022; Coughlin, Greenbaum, Titchen, 2020; Titchen et al, 2017; Richie-Zavaleta et al, 2019; United States Department of Justice (US DOJ), 2016; Miller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lederer and Wetzel surveyed over 100 survivors of sex trafficking in a study, and 63% of the survivors reported going to an emergency room while being trafficked(Tiller & Reynolds, 2020). Trafficked persons may present to a variety of health settings, including an emergency room, urgent care, obstetrician or gynecologist, primary care physician, and dentist(Coughlin et al, 2020). Because of the violent nature of human trafficking, girls often experience physical injuries and seek medical care(Armstrong & Greenbaum, 2019;Hachey & Phillippi, 2017).…”
mentioning
confidence: 99%